2021
DOI: 10.1111/anae.15483
|View full text |Cite
|
Sign up to set email alerts
|

Anaemia among intensive care unit survivors and association with days alive and at home: an observational study

Abstract: Summary Anaemia is highly prevalent at the time of intensive care unit discharge and is persistent for a high proportion of intensive care unit survivors. Whether anaemia is a driver of impaired recovery after critical illness is uncertain. The aim of this study was to test the hypothesis that, in adult intensive care survivors, anaemia at the time of intensive care unit discharge independently predicts decreased days at home‐90. This retrospective cohort study was conducted in a tertiary intensive care unit i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 20 publications
2
17
0
Order By: Relevance
“…The consequences of anemia in this patient population are severe compared to non-intensive care patients [68]. In a retrospective study from Van der Laan et al, the presence of anemia at ICU discharge was an independent risk factor for a worse outcome [69]. Additionally, an observational study by Smilowitz et al, including >3000 patients, identified anemia as a predictor of reduced long-term survival [70].…”
Section: Discussionmentioning
confidence: 99%
“…The consequences of anemia in this patient population are severe compared to non-intensive care patients [68]. In a retrospective study from Van der Laan et al, the presence of anemia at ICU discharge was an independent risk factor for a worse outcome [69]. Additionally, an observational study by Smilowitz et al, including >3000 patients, identified anemia as a predictor of reduced long-term survival [70].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, van der Laan et al analysing 6,358 ICU survivors, mainly discharged from surgical ICU (60.7%, 3860/6358), in Western Australia, found that 45.4% (2,886/6,358) of patients had anaemia (<10 g/dL), which correlated with decreased days at home till day-90 (Relative risk 0.96, 95% CI 0.93-0.98). [4] Notably, anaemia in critically ill patients appears to be a lasting issue. Warner et al analysed levels of haemoglobin at 3-month, 6-month, and 12-month after ICU discharge among 6,901 critically ill patients in Minnesota and reported that the prevalence of anaemia at 3-month, 6-month, and 12-month were 56%, 52%, and 45%, respectively [21].…”
Section: Discussionmentioning
confidence: 99%
“…Anaemia is a highly prevalent comorbidity in critically ill surgical patients, and it is estimated that approximately 50% of critically ill patients experience anaemia. [1][2][3][4] A number of evidence have shown that anaemia has a deleterious impact on the outcome in patients undergoing surgery. [5][6][7] Baron et al conducted a multicentre study with 39,309 patients undergoing in-patient surgery in 28 European nations and implicated anaemia with poor postsurgery outcomes, including hospital length of stay, postoperative admission to intensive care, and in-hospital mortality [5].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, longer ICU treatment is positively correlated with the development of severe anaemia [10]. In addition, anaemia often persists in the first year after hospital discharge [4 ▪ ] and is an independent risk factor for morbidity and mortality [3,7 ▪▪ ,11 ▪ ,12–14]…”
Section: Introductionmentioning
confidence: 99%